Biosynthesized colloidal silver and gold nanoparticles as emerging leishmanicidal agents: an insight. (December 2017) - Ovais, Muhammad; Nadhman, Akhtar; Khalil, Ali Talha; Raza, Abida; Khuda, Fazli; Sohail, Muhammad Farhan; , Zakiullah; Islam, Nazar Ul; Sarwar, Hafiz Shoaib; Shahnaz, Gul; Ahmad, Irshad; Saravanan, Muthupandian; et al.
Many recent key innovations in nanotechnology have greatly fascinated scientists to explore new avenues in treatment and diagnosis of emerging diseases. Due to extensive utilization of metallic nanoparticles (NPs) in diverse biomedical applications, scientists are looking forward to green synthesis of NPs as safer, simple, fast, and low-cost method over chemical and physical methods. Due to enriched phytochemistry, no need for maintenance and ready availability, plants are preferred for green synthesis of silver (AgNPs) and gold NPs (AuNPs). Recently, several researchers have exploited these biogenic NPs as potential antileishmanial agents. The current article is focused to mechanistically explain the antileishmanial activity of biogenic AuNPs and AgNPs with a futuristic discussion on the faith of these particles as emerging antileishmanial agents.